Encapsulation of Amazonian Blueberry juices: Evaluation of bioactive compounds and stability - Mar, Josiana Moreira; Silva, Laiane S.; Rabelo, Maxwaldo da S.; Muniz, Magno Perêa; Nunomura, Sergio Massayoshi; Correa, Renilto F.; Kinupp, Valdely Ferreira; Campelo-Felix, Pedro Henrique; Bezerra, Jaqueline de Araújo; Sanches, Edgar Aparecido (LWT, 2020)
Bioactive compounds of Clidemia japurensis and Clidemia hirta juices were encapsulated in maltodextrin (MD) of different dextrose equivalents (DE – MD10, MD20 AND MD30). Microparticles containing the encapsulated juices were obtained by freeze-drying process. The stability of the encapsulated bioactive compounds was evaluated under different relative humidity (22 and 77%) at 25 °C by DPPH and ABTS methods. Twelve bioactive compounds were identified by UFLC-Q-TOF-MS/MS and classified as organic acids, flavonoids and anthocyanins. The juices presented good antioxidant properties [DPPH value of 943 ± 15 (C. japurensis) and 994 ± 14 μM TE (C. hirta); ABTS value of 1119 ± 24 (C. japurensis) and 1273 ± 18 μM TE (C. hirta)]. Encapsulation Efficiency (EE) ranged from 97.0 to 99.8% (DPPH) and from 87.8 to 99.1% (ABTS). The encapsulated juices did not present activity water (AW) values that could favor microbial growth. The powdered juices prepared using lower DE carrier resulted in better retention and stability of the bioactive compounds due to the low water adsorption According to the ABTS results, the bioactive compounds of C. hirta and C. japurensis encapsulated in MD10 carrier and stored at RH = 22% presented half-life time around 45 and 37 days, respectively. These results represent an interesting possibility of application in food industry. © 2020
Keywords: Dextrose; Encapsulation; Low Temperature Drying; Bioactive Compounds; Clidemia Hirta; Clidemia Japurensis; Dextrose Equivalents; Freeze Drying; Uflc-q-tof-ms/ms; Inductively Coupled Plasma